Diversity and distribution of microfungi in foliage leaf, bark and leaf litter of Couroupita guianensis - Venkatesan, G.; Sharavanan, P. S. (Current Botany, 2020)
The diversity and distribution of micro fungal assemblages in the foliage leaf, bark and leaf litter tissues of the Couroupita guianensis sacred plant. For the host, we recorded 1005 fungal species isolates from 900 tissue segments. A total of 62 fungal species were isolated from foliar endophytes, phellophytes and leaf litter. The colonization frequency of the fungi species has been recorded as 111.66% from the endophytes, phellophytes and leaf tissues. The fungi species recovered in various groups included ascomycetes, coelomycetes, hyphomycetes, zygomycetes and sterile fungi. The number of fungal species is increased for the plant tissues, it showed that the species diversity is increasing. A correspondence analysis also showed that the fungal species assemblages were different from each type of tissue.